Rethinking Pediatric Sepsis and Septic Shock: Beyond International Consensus Criteria - Shamavu GK; Mohamoud F (Pediatric Health, Medicine and Therapeutics)
Gabriel Kakuru Shamavu, Fatima Mohamoud Department of Pediatrics, Faculty of Clinical Medicine and Dentistry, Kampala International University Western Campus, Ishaka-Bushenyi, UgandaCorrespondence: Gabriel Kakuru Shamavu, Department of Pediatrics, Faculty of Clinical Medicine and Dentistry, Kampala International University Western Campus, Ishaka-Bushenyi, Uganda, Email gabrielshamavu@gmail.com; shamavu.kakuru@studwc.kiu.ac.ugPurpose/Objective: International pediatric sepsis consensus definitions play a critical role in evidence-based clinical practice, providing standardized tools for case identification. However, a common misconception is treating sepsis as a static diagnosis rather than recognizing it as a dynamic and evolving process. It is essential to integrate consensus criteria into a broader, more flexible clinical approach rather than applying them rigidly.Materials/Methods – Literature Review: This expert commentary compares past and current pediatric sepsis definitions, analyzing their clinical implications, supporting evidence, and feasibility across diverse healthcare settings.Findings/Results: The transition from a Systemic Inflammatory Response Syndrome-based model (2005 International Pediatric Sepsis Consensus Conference) to an organ dysfunction-based model (Phoenix Sepsis Score 2024) has improved specificity but may also delay early recognition by requiring established organ dysfunction.Conclusion and Recommendations: Sepsis should be viewed as a continuum rather than a static state. This commentary does not oppose sepsis consensus criteria but advocates for clinicians to apply clinical judgment beyond them. Future definitions should balance specificity with early recognition while allowing for clinical adaptability in various healthcare contexts.Keywords: sepsis, septic shock, pediatric, criteria, organ dysfunction